Interdigitated electric-magnetic gradient MXene-based nanocomposite films for concurrent high-efficiency electromagnetic shielding and sensitive detection - Lingfeng Yu; Yanni Yang; Shulong Chang; Yihao Xiao; Song Luo; Shichun Hao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Nickel incorporation engineering for synergistic regulation of oxygen vacancies and electronic band configuration in Bi2O3 nanosheets for high-performance supercapacitor electrodes - Lingfeng Li; Weihao Zhang; Xuexuan Luo; Xueyi Chang; Muqing Chen; Zhiyu Cheng; Yongfu Qiu; Yu Wang (Chemical Engineering Journal, 2026)

Research on the mechanical properties and residual strength prediction model of an old loess landslide - Xican Cui; Lingfeng Zhao; Yasheng Luo; Kaihao Zheng; Chengbin Zhao (Natural Hazards, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Environmental changes in the Okinawa Trough over the last 88 ka BP: Evidence from high-resolution bulk mineralogy - Lingfeng Luo; Xuguang Feng; Jianjun Zou; Xisheng Fang; Xinru Xue; Ruxi Dou; Baohua Han; Qingchao Wang; Aimei Zhu; Zhi Dong; Gang Yang; Xuefa Shi (Marine Geology, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Evaluating the propagation characteristics of meteorological drought to hydrological drought using a three-dimensional method - Xiaoli Yang; Lingfeng Xie; Ding Luo; Zhoubing Ye (Journal of Hydrology, 2025)

Propagation characteristics of meteorological drought to hydrological drought in China - Ding Luo; Xiaoli Yang; Lingfeng Xie; Zhoubing Ye; Liliang Ren; Linyan Zhang; Fan Wu; Donglai Jiao (Journal of Hydrology, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Processes determining the seasonality of accelerated Tibetan Plateau warming during recent decades - Mengchu Zhao; Xiu-Qun Yang; Lingfeng Tao; Jing-Jia Luo (Climate Dynamics, 2025)

Abrupt enhanced Pacific warm water intrusion into the Sea of Okhotsk since the early Holocene - Xuguang Feng; Jianjun Zou; Xuefa Shi; Zhengquan Yao; Zhi Dong; Jiang Dong; Yonghua Wu; Ruxi Dou; Hualong Jin; Aimei Zhu; Xiaojing Wang; Qingchao Wang; et al. (Quaternary Science Reviews, 2024)

Targeting gut-brain axis by dietary flavonoids ameliorate aging-related cognition decline: Evidences and mechanisms - Zhongxing Chu; Shuai Han; Yi Luo; Yaping Zhou; Lingfeng Zhu; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2024)

Time-varying associations of patient and tumor characteristics with cancer survival: an analysis of SEER data across 14 cancer sites, 2004–2017 - Emily K. Roberts; Lingfeng Luo; Alison M. Mondul; Mousumi Banerjee; Christine M. Veenstra; Angela B. Mariotto; Matthew J. Schipper; Kevin He; Jeremy M. G. Taylor; Andrew F. Brouwer (Cancer Causes & Control, 2024)

Potential high-risk release sources of thallium and arsenic from surrounding rocks of a typical thallium and arsenic mining area in southwest China - Yanpei Du; Lingfeng Shi; Xinyan Cao; Fengqi Zhao; Pengjie Hu; Rongrong Ying; Shangyi Gu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Effects of cadmium exposure during pregnancy on genome-wide DNA methylation and the CREB/CREM pathway in the testes of male offspring rats - Xiushuai Du; Jianlin Zhu; Xueming Xu; Zhilan Lu; Xiaoqin Li; Yuchen Li; Lingfeng Luo; Wenchang Zhang; Jin Liu (Chemosphere, 2024)

Water-dispersible colloids facilitate the release of potentially toxic elements from contaminated soil under simulated long-term acid rain - Juan Liu; Lingfeng Shi; Yanpei Du; Xueting Luo; Pengjie Hu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Paternal genetic intergenerational and transgenerational effects of cadmium exposure on hormone synthesis disorders in progeny ovarian granulosa cells - Yi Sun; Chenyun Zhang; Lingfeng Luo; Hao Lin; Chenchen Liu; Wenchang Zhang (Environmental Pollution, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Study on bioleaching of heavy metals and resource potential from tannery yard sludge - Hang Liu; Kaizhi Yang; Lingfeng Luo; Qian Lu; Yonggui Wu; Meiyan Lan; Youfa Luo; Wan Liang (Environmental Science and Pollution Research, 2021)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)